Cooling Powder Against Dark Spots With Curcuma Longa Linn And Cananga Odorata - Puspitasari, Yesi; Hasanah, Ulfatul; Lailiyah, Nurul (UNIVERSITAS MUHAMMADIYAH MATARAM, 2025)
Cosmetics are one of the skin care efforts, in addition to protecting the skin from ultraviolet rays, cosmetics function to brighten the skin, clean the skin, and moisturize the skin. Excessive exposure to sunlight causes skin damage, so it needs care to protect the skin. Natural cosmetics that use natural ingredients are safer to use and tend not to have side effects. One of the natural cosmetics for skin care is cold powder, which is one of the traditional powders for treating the skin. The purpose of the team's community service is to find out the Curcuma Longa Linn and Cananga Odorata cold powder, this community service uses a quantitative method. The results of the cold powder community service The marketing results of Curcuma Longa Linn and Cananga Odorata cold powder on the marketing percentage for Curcuma Longa Linn Cananga Ordata on the first day were 31.57% while Curcuma Longa Linn Canangan Ordata on the second day was 57.90% and many positive responses from the people who use it.